Pipecolic acid in plants: biosynthesis, signalling, and role under stress - Fatma Nur Koc; Burcu Seckin Dinler (Botanica, 2022)
Plants protect themselves by developing defensive responses against various biotic and abiotic stress factors throughout their lives. As a result, they create a stress response called ʻsystemic acquired resistance’ (SAR) under pathogen infection. Pipecolic acid is one of the critical signalling molecules in regulating systemic acquired resistance, and it is a product of L-lysine metabolism in all organisms. It is synthesised not only by plants but also by microorganisms, animals and fungi. Many studies have been carried out to understand pipecolic acid’s biosynthesis, transport and role in plants under biotic stress. But recent studies report that pipecolic acid also functions as a stress response in plants under abiotic stress. This paper reviews the historical development of studies on pipecolic acid, its biosynthesis, and its function in plants under stress conditions and systemic acquired resistance.